Deteksi Dini Masalah Kesehatan Reproduksi Melalui Pos Kesehatan Remaja - Wilda Rezki Pratiwi; Hamdiyah Hamdiyah; Asnuddin Asnuddin (University of Islam Malang, 2020)
Marioriawa is one of the sub-districts located in Soppeng Regency with an area of 320 Km2 cover by 5 villages (Bulue, Laringgi, Patampanua, Panincong, Tellulimpoe and 5 villages (AttangSalo, Batu-Batu, Limpomajang, Manorang Salo, Attang Salo) with average population of 27,512 with a density of 86 people/km2. In Marioriawa there are 2 high schools (SMAN 01 Soppeng and SMK 02 Soppeng).The students in SMAN 01 Soppeng classified to adolescents in Soppeng Regency precisely in Laringgi village a total of 487 people have not been fully checked out regularly and the discovery of several cases of pregnancy outside marriage, early marriage, HIV/AIDS in rural areas and adolescent health problems (anemia, stunting, KEK and obesity). This is a problem because, lack of adolescent knowledge about health reproduction, identification of new health problems found at the time the teenager will become ca lon mother / father, due to lack of early detection in their teens. It's just that physical growth in adolescents is not always accompanied by the maturity of thinking and emotional abilities. In addition, in adolescence there is also a process of self-introduction, and failure in the process of self-introduction can cause various problems.The method used is the lecture method with health education and adolescent health checks through the establishment of adolescent health posts (PKR) in collaboration with the School Health Unit (UKS) at SMAN 01 Soppeng. The results of the activity are an increase in knowledge after giving material about adolescent health, checking vital signs, HbSAg examination, physical examination of adolescents, HIV testing, and hemoglobin examination. From the results of the examination found that 86 adolescents were found to suffer from mild anemia with hemoglobin levels below 10 gr / dl, as many as 1 person infected with HBsAg, 2 people found a lump in the breast and no HIV patients were found in adolescents. Conclusions are able to detect symptoms / signs early if certain diseases occur in him that are related to the reproductive system, adolescents in rural areas free from sexually transmitted diseases (STDs) and the importance of education to check themselves routinely before they become prospective parents. Suggestion of support from parents to carry out routine health check-up of their children not only to do health check at the time the child / teen complains of pain in certain body part.